2021
DOI: 10.1099/jgv.0.001627
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine and pyrimethamine inhibit the replication of human respiratory syncytial virus A

Abstract: Human respiratory syncytial virus (hRSV) is a major cause of respiratory illness in young children and can cause severe infections in the elderly or in immunocompromised adults. To date, there is no vaccine to prevent hRSV infections, and disease management is limited to preventive care by palivizumab in infants and supportive care for adults. Intervention with small-molecule antivirals specific for hRSV represents a good alternative, but no such compounds are currently approved. The investigation of existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(93 reference statements)
1
2
0
Order By: Relevance
“…Similar to previous reports (Khatun et al, 2015;Tian and Meng, 2016), ribavirin and 5-Fluorouracil inhibited the infection of reporter virus with the IC50 doses at 94.58 and 220.1 μM (Figures 4D-E), respectively. Chloroquine, an anti-malaria drug, was identified as a broadspectrum antiviral drug against many RNA viruses, such as SARS-CoV-2 (Liu et al, 2020), human respiratory syncytial virus (Rahman et al, 2021), and hantavirus (Vergote et al, 2021). We also observed the inhibitory effect of chloroquine against PRRSV.…”
Section: Antiviral Assay Against Prrsv Using Rta-gluc2 Reporter Virussupporting
confidence: 66%
“…Similar to previous reports (Khatun et al, 2015;Tian and Meng, 2016), ribavirin and 5-Fluorouracil inhibited the infection of reporter virus with the IC50 doses at 94.58 and 220.1 μM (Figures 4D-E), respectively. Chloroquine, an anti-malaria drug, was identified as a broadspectrum antiviral drug against many RNA viruses, such as SARS-CoV-2 (Liu et al, 2020), human respiratory syncytial virus (Rahman et al, 2021), and hantavirus (Vergote et al, 2021). We also observed the inhibitory effect of chloroquine against PRRSV.…”
Section: Antiviral Assay Against Prrsv Using Rta-gluc2 Reporter Virussupporting
confidence: 66%
“…Mice were kept in cages inside stainless steel isolation cabinets for infection tests, and the air was filtered with highefficiency particle air ventilation. At day 0, mice were given a ketamine and xylazine mixture (43 mg/kg and 5 mg/kg, respectively) to make them unconscious before being given 20 µl of a PBS solution containing the A/PR/8/34 virus intranasally, as previously described (Rahman, et al, 2021). Infection was performed with either 500 or 750 Plaque-Forming Units (PFU).…”
Section: J In Vivo Experimentsmentioning
confidence: 99%
“…It has been shown that the administration of chloroquine, a typical inhibitor of autophagy, in a mouse model led to the inhibition of human Respiratory Syncytial Virus A (long strain) replication [ 103 ], which makes chloroquine a potential drug for the therapeutic treatment of RSV infection. RSV infection is involved in the subsequent development of clinical manifestations such as asthma [ 104 ].…”
Section: Autophagy In Lung Infectionsmentioning
confidence: 99%